Bi-Template Assisted Sol-Gel Synthesis of Photocatalytically-Active Mesoporous Anatase TiO2 Nanoparticles - Hamisu, Abubakar; Gaya, Umar Ibrahim; Abdullah, Abdul Halim (Applied Science and Engineering Progress, 2021)
Sol-gel mesoporous titanium dioxide powders have been synthesized from chitosan and/or hexadecyltrimethylammonium bromide (HDTMA) and characterized using x-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), ultraviolet-visible (UV-vis) spectroscopy, thermogravimetric analysis (TGA), differential thermal analysis (DTA) and N2 adsorption-desorption measurements. The photocatalytic performance of the synthesized meso-TiO2 powders was optimized based on the central composite design (CCD) of methyl orange (MO) degradation under UV light irradiation. The maximum MO degradation was 62.3% over a period of 60 min. Oxides produced using the binary chitosan and HDTMA template (C,H-TiO2) exhibited the relatively higher surface area (99.5 m2/g), smaller crystal size (12.78 nm), narrower band-gap energy (2.92 eV) and higher photocatalytic rate constant (0.0112 min–1) than as those from chitosan (C/TiO2) or HDTMA (H/TiO2) as the template.